(untitled) (Temporalis, 2026)
This article aims to discuss the most recurrent misunderstandings surrounding the critical social theory of bourgeois society and the Marxist scientific method. It demonstrates how such distortions, often derived from positivist or fragmented readings, undermine the comprehension of social totality and the historical and contradictory nature of reality. Briefly, it emphasizes the relevance of the Marxian method for analyzing capitalist society and for constructing scientific knowledge committed to social transformation. Furthermore, it highlights the importance of critically engaging with the historical-dialectical materialism within Postgraduate studies in Social Work, given its potential to provide theoretical and methodological mediations for understanding reality in its complexity and processuality.